A multicenter prospective registration study on laparoscopic pancreatectomy in Japan: report on the assessment of 1, 429 patients. (11th December 2019) - Ohtsuka, Takao; Nagakawa, Yuichi; Toyama, Hirochika; Takeda, Yutaka; Maeda, Atsuyuki; Kumamoto, Yusuke; Nakamura, Yoshiharu; Hashida, Kazuki; Honda, Goro; Fukuzawa, Kengo; Toyoda, Eiji; Tanabe, Minoru; et al.
Abstract: Background: Prospective studies are needed to understand the safety and feasibility of laparoscopic pancreatectomy. The aim of the present study was to describe laparoscopic pancreatectomy currently undertaken in Japan, using a prospective registration system. Methods: Patient characteristics and planned operations were registered preoperatively, and then the performed operation and outcomes were reported using an online system. Collected data were also compared between institutions based on their level of experience. This study was registered with UMIN000022836. Results: Available data were obtained from 1, 429 patients at 100 Japanese institutions, including 1, 197 laparoscopic distal pancreatectomies (LDPs) and 232 laparoscopic pancreatoduodenectomies (LPDs). The rates of completion for planned operations were 92% for LDP and 91% for LPD. Postoperative complication rates after LDP and LPD were 17% and 30%, and 90‐day mortality rates were 0.3% and 0.4%, respectively. Shorter operation time, less blood loss, and lower incidence of pancreatic fistula were observed in institutions experienced in LDP. A higher rate of pure laparoscopic procedure and shorter operation time were noted in institutions experienced with LPD. Conclusion: LDPs and LPDs are performed safely in Japan, especially in experienced institutions. Our data could support the next challenges in the field of laparoscopic pancreatectomy. Abstract : Highlight This study aimed to describe laparoscopic pancreatectomy currently undertaken in Japan, using a prospective registration system. Data obtained from 1, 429 patients at 100 Japanese institutions were assessed. Ohtsuka and colleagues concluded that laparoscopic pancreatectomy is performed safely in Japan, especially at experienced institutions, supporting the next challenges facing laparoscopic pancreatectomy.